Report on Proceedings of the Fourteenth Annual European CME Forum, Studio Hybrid from Manchester UK, November, 2021. Issue 1 (31st December 2022) - Murray, Ron
ABSTRACT: In a departure from the increasingly familiar virtual meetings conducted via collaboration apps the Fourteenth Annual European CME Forum (#14ECF) took place between 3 and 5 November 2021 using a blended model that relied mainly on a studio-based hub. A small group of faculty hosted plenary sessions in the studio with participation by attendees, panellists and workshop leaders via an interactive online meeting platform. The theme of the meeting was "The 3-legged stool: Achieving balance for effective CME. The plenaries focused on three linked topics, Rules and Regulations, Educational Design and Outcomes, and Funding and Independence. These were broadcast in high definition whilst interaction among participants, workshop leaders, and poster authors was achieved using an avatar-based conferencing platform. The breakout workshops covered topics including digital literacy, international collaboration, artificial intelligence, and diversity and inclusion. The meeting format was well accepted by participants and will form the basis for more hybrid-type meetings for future meetings. Graphical Abstract: uf0001